Extraction of Nb(v) by quaternary ammonium-based solvents: toward organic hexaniobate systems. Issue 48 (22nd November 2016) - Deblonde, Gauthier J-P.; Chagnes, Alexandre; Roux, Marie-Aude; Weigel, Valérie; Cote, Gérard
Abstract : A new liquid–liquid extraction system has been developed for the rapid and easy transfer of hexaniobates (H x Nb6 O19 x −8 ) into organic solvents. Abstract : Solvent extraction of Nb(v ) from alkaline aqueous media using quaternary ammonium solutions, especially Aliquat® 336 diluted in an aliphatic diluent, was investigated. The hexaniobate ions (H x Nb6 O19 x −8 ) were extracted into the organic phase with very high yields at room temperature and within a few minutes, affording easy access to organic solutions of hexaniobates. Several parameters were found to influence the extraction of H x Nb6 O19 x −8 including the nature and concentration of alkali cations, confirming subtle effects previously described for polyoxoniobates such as ion-pairing with alkali ions. The extraction of H x Nb6 O19 x −8 with Aliquat® 336 is also influenced if competing anions are present in the aqueous phase (NO3 −, Cl −, C2 O4 2−, SO4 2− and CO3 2− ) and varies with the pH mainly due to the competitive extraction of hydroxide ions at high pH. The co-extraction of sodium ions with H x Nb6 O19 x −8 was observed as well as the co-extraction of water molecules, suggesting a self-association of the extractant. The proposed liquid–liquid extraction generic system paves the way for innovative niobium (and potentially tantalum) hydrometallurgical processes and it may also afford more direct routes for exploring the chemistry of hexaniobates in organic solvents.